The determinants of saving behaviour among Valiram Group employees / Nur Azmina Syamim Kamarudin - Kamarudin, Nur Azmina Syamim (2014)
Over the years, numerous researchers have studied on the determinants of Saving behavior among the households and employees. Therefore, this research is aims to investigate whether Monthly income, financial literacy (FL), and Rates of return (ROR) have significant influence on the saving behaviour (SB) among Valiram Group Employees. Primary data are collected using self-administered questionnaire. The samples comprised 100 employees from four departments among Valiram Group Employees. Meanwhile, Pearson Correlations and Multiple Regression Analysis are employed to identify whether the three factors have relationship with the saving behaviour of the employees. The findings show that all the MI, FL and ROR have positive relationship with SB while MI has the greatest impact on SB among the four independent variables. This signifies that parents are playing important roles in ensuring their children to establish saving behaviour. In practical, this research can contribute to the retail banks in designing effective strategies to penetrate the young savers specifically for employees below 25 years old. Besides, it also enlightens the policy makers to stimulate savings among the employees via raising their financial literacy.